2015
DOI: 10.3349/ymj.2015.56.2.311
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Features of Erionite-Induced Malignant Mesothelioma

Abstract: This review analytically examines the published data for erionite-related malignant pleural mesothelioma (E-MPM) and any data to support a genetically predisposed mechanism to erionite fiber carcinogenesis. Adult patients of age ≥18 years with erionite-related pleural diseases and genetically predisposed mechanisms to erionite carcinogenesis were included, while exclusion criteria included asbestos- or tremolite-related pleural diseases. The search was limited to human studies though not limited to a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Interestingly, Ballirano et al [48] showed that both erionite-Na from Rome (OR, USA) and woolly erionite-K from Durkee (OR, USA) could fix Fe(II) into the structure through ion-exchange involving mainly Na. Further, the amount of Fe(II) bound by sample in this study [330 (20) nmol/mg] is comparable with that acquired, under the same experimental conditions, by erionite-Na from Rome (OR, USA) [262(1) nmol/mg]. These data are relevant considering the reported higher selectivity of erionite for Ca with respect to Na [68,69], and provide evidence of a strong tendency of Fe(II) to enter the erionite structure, due to its relatively high ionic potential, which exceeds that of the common extra-framework cations [50].…”
Section: Fe(ii) Binding To Erionite and Chemical Characterizationmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, Ballirano et al [48] showed that both erionite-Na from Rome (OR, USA) and woolly erionite-K from Durkee (OR, USA) could fix Fe(II) into the structure through ion-exchange involving mainly Na. Further, the amount of Fe(II) bound by sample in this study [330 (20) nmol/mg] is comparable with that acquired, under the same experimental conditions, by erionite-Na from Rome (OR, USA) [262(1) nmol/mg]. These data are relevant considering the reported higher selectivity of erionite for Ca with respect to Na [68,69], and provide evidence of a strong tendency of Fe(II) to enter the erionite structure, due to its relatively high ionic potential, which exceeds that of the common extra-framework cations [50].…”
Section: Fe(ii) Binding To Erionite and Chemical Characterizationmentioning
confidence: 97%
“…Inhalation of fibrous erionite has shown to be correlated with diseases like those already known from exposure to asbestos [14,15]. In particular, high rates of malignant mesothelioma were reported, since the 1970s, in three villages of Cappadocia, Turkey [16][17][18][19][20]. In vivo and in vitro studies indicated that fibrous erionite is significantly more tumorigenic than chrysotile asbestos and amphibole asbestos [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…There were five cohort studies that investigated cases of MM survival. 30,33,34,59,60 Nine studies used a case-control design, 29,[33][34][35][36]44,51,60,64 two of which were nested case-control studies. 44,60 There were two risk assessment studies that used modeling approaches to estimate MM mortality 58 and incidence.…”
Section: Data Source and Study Designmentioning
confidence: 99%
“…Average annual precipitation is around 15 inches (380 mm). (101) There is an average of 19.7 days per year with at least 0.01 inches of precipitation according weather data collected from 1981 to 2010 from the NOAA National Climatic Data Center. (104) According to the 2010 U.S. Census Bureau, Harding County has a total area of 2,678 square miles and a population of 1,255.…”
Section: Description Of the Investigatory Sitementioning
confidence: 99%
“…Erionite is an acicular zeolite and it has been shown that people exposed to erionite have a higher risk to develop malignant mesothelioma (MM) than people exposed to all the other mineral fibers that are currently exposure regulated in the United States. (101) Although erionite does not have the same extensive and various commercial applications as the other regulated asbestos fibers and is rarely found in the environment, disturbance of natural-occurring erionite at specific sites may generate airborne fibers with similar or even worse health effects as the well-known asbestos fibers.…”
Section: Introductionmentioning
confidence: 99%